Finite element analysis of RC beams strengthened with bamboo fibre reinforced composite plate using ANSYS - Anas, Shamsudin (2018)
Presence of opening in reinforced concrete (RC) beam automatically reduce the load capacity of the RC beams significantly followed by excessive cracking and deflection. To recover the loss in strength, carbon reinforced polymer (CFRP) which is one of synthetic fibre was opted to be used as strengthening material. In addition, CFRP provide a relatively high additional strength for beam. However, in order to promote the usage of CFRP in construction today, the high cost of CFRP was proved to be a hindrance. On the contrary, natural fibre polymer which is more sustainable and cheaper was a perfect alternative to synthetic fibre. The main objective of this research was to study on the behaviour and potential of bamboo reinforced composite plate as the strengthening material. Several beams with dimensions of 120 x 300 mm and a length of 1500 mm were modelled in three-dimensional (3D) as simply-supported beams in ANSYS+CivilFEM 12.0. In this research, there were three (3) types of configurations for beams that were analysed which are conventional beam, beam unstrengthened at flexural and beam with openings. The beam was further enhanced with BFRCP to check the reliability of BFRCP. Finite element analysis (FEA) was implemented to obtain certain results which are the load-deflection curve, crack pattern, stress contours and strain contours. From FEA, the RC beam undergone a reduction of 10.8% in terms of load bearing capacity when the stirrups at the flexural zone were removed. Then, application of BFRCP asstrengthening material at flexural zone managed to regain 71.1% of the strength loss which almost the same as the original strength. A huge load capacity loss occured when opening was created in the beam with a percentage loss of 47.4%. Application of BFRCP at the shear zone managed to regain 38% of strength loss. After that, FEA results and experimental results were validated. For solid beam, the load-deflection curve showed a strong agreement with percentage difference of 0.3%. For beam unstrengthened at flexural, the difference 1.8% which proved a strong agreement obtained. Beam strengthened at flexural with BFRCP showed a strong agreement as the percentage difference was 1.4% only. Beam with openings also in a strong agreement with percentage difference of 4.7%. Beam with openings strengthened with BFRCP reached a comparable agreement with percentage difference of 19.5% which is still within permissible range. In terms of crack patterns, a strong agreements between all results of FEA and experimental results were obtained. As conclusion, bamboo fibre composite plate can be an alternative external strengthening material for structural strengthening.